Pengenalan Lapangan Persekolahan oleh Mahasiswa Universitas Muhammadyah Riau di Pondok Pesantren Dar-El Hikmah Pekanbaru - Tiara Fitri; Rika Novita Manda Sari; Vitriani Vitriani (Lembaga Pengembangan Kinerja Dosen, 2025)
Education plays a crucial role in improving human resource quality to achieve national goals. Universitas Muhammadiyah Riau (UMRI), through the Faculty of Teacher Training and Education (FKIP) Informatics, equips students with academic and pedagogical competencies to produce professional future teachers. The School Field Introduction Program (PLP) at Ma Dar-El Hikmah Pekanbaru serves as an experiential learning platform that enables students to observe school culture, build competencies, and understand the teaching-learning process directly. This study employs observation, interviews, and documentation methods to provide in-depth insights into the teacher’s role in managing the educational environment. The findings of this program are expected to enhance students’ understanding of the education sector and develop their skills as professional and adaptive future educators.